Trends of Rotavirus Diarrhea in Hospitalized Children in Yogyakarta Year 2013 –2015 - Nenny Sri Mulyani; Dian Anggraini; Retno Palupi Baroto; Asal Wahyuni Erlin Mulyadi; Rizki Anindita; Yati Soenarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Diarrhea, together with pneumonia, is accountable for 25% death of children under five globally (IVAC, 2017). In Indonesia, diarrhea is also among the top ten diseases of cause of death in children under five (WHO, 2015). Rotavirus diarrhea is responsible for 60% in 2006 (Soenarto et al, 2009) of children diarrhea in Indonesia. Rotavirus vaccine in Indonesia was introduced commercially in 2011, nonetheless its use was reportedly low. Despite the declining rate of rotavirus incidence, surveillance is important to show the burden of rotavirus diarrhea in children. Thus, this study aims to describe the incidence of rotavirus diarrhea in hospitalized children under five in Yogyakarta province. This was a prospective study, conducted in two participating hospitals in Yogyakarta: RSUP Sardjito Yogyakarta and RSUD Wates from January 2013 – December 2015. This study is a part of the Indonesia surveilance entitled “Hospital-based surveillance of rotavirus diarrhea in children in Indonesia”, enrolling children under five hospitalized due to acute watery diarrhea. The questionare was modified from the WHO generic protocol of rotavirus surveillance (WHO, 2002). Data collection was perfomed after informed consent was signed by parent or guardian. The stool samples were tested for rotavirus with the EIA test and tested for genotyping with RT-PCR. The data were analysed and presented using descriptive analytic method. Of 684 eligible patients hospitalized with acute watery diarrhea, 557 subjects were enrolled with 518 feces were tested for rotavirus. The percentage of rotavirus incidence in year 2013, 2014, and 2015 were 37%, 41% and 61 % respectively. The predominant rotavirus genotyping was G3P [8]. Rotavirus mostly found in children age 6 – 23 months (55 %), and was identified more in male than female (62 % vs 38%). During the 3 years study period, rotavirus occurred all year round, and showed to reach its peak on January 2015. Rotavirus positive diarrhea commonly presented with dehydration (79%) compare to negative rotavirus diarrhea (55%). It indicated that the incidence rate of rotavirus diarrhea in Yogyakarta is quite high and rotavirus diarrhea remains as significant contributor to hospitalized children with diarrhea. The trend of rotavirus diarrhea in children under 5 years increased over the years’ period. The rotavirus diarrhea mostly presented with dehydration, thus rotavirus diarrhea remains as significant contributor to hospitalized children with diarrhea. This shows an evidence that the burden of rotavirus diarrhea in children under 5 years remains prominent.